Phytoplankton diversity and abundance during a bloom of Pyrodinium bahamense in Irong-Irong Bay, Samar, Philippines from September 2016 to January 2017 - Baronda, Aldwin Matthew M. (2017)
The dinoflagellate species Pyrodinium bahamense is the main causative agent of red tide events in Eastern Visayas for the last three decades. The community of Irong-Irong Bay depends largely on mariculture and red tide events cause great economic losses. This study then aimed to monitor the phytoplankton composition and density of Irong-Irong Bay during the period of the P. bahamense bloom and to provide an update on the status of the water quality. Monthly sampling was conducted from September 2016 to January 2017. Qualitative (50 mL) and quantitative (1 L) phytoplankton samples were collected in triplicates through horizontal towing of a 20 um sized plankton net and the bucket method, respectively. Physico-chemical parameters (e.g. temperature, salinity, pH, light intensity, depth, turbidity) were measured in situ and water samples were collected for nutrient analysis (e.g. nitrates and chlorophyll-a). Results showed that P. bahamense reached its peak density at 1.66 x 10 raised to the power of 4 cells L raised to negative 1 during November and dominated during the first three months of sampling. The species Nitzschia elongata and Pseudo-nitzschia spp. dominated during December 2016 and January 2017. The diversity was highest during the month of January due to favourable conditions for phytoplankton growth. The factors that may have affected the growth and abundance of P. bahamense are relatively low temperatures, high amounts of rainfall, penetration of light to the sediments, and the grazing of the dinoflagellate Noctiluca scintillans.